Kemitraan Kebijakan dalam Mewujudkan Kemandirian Desa - Adnan, Hasyim (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Policy partnerships between village governments, communities, and the private sector are key in realising village independence. This research analyses the role of policy partnerships in improving the welfare of village communities and accelerating village development. The research method used is literature study and case analysis. The results show that policy partnerships can encourage innovation, improve the efficiency of resource use, and strengthen community participation in village development. However, challenges such as weak coordination and differences in interests can hinder the success of policy partnerships.